Factors associated with cognitive impairment in elderly versus nonelderly patients with metabolic syndrome: The different roles of FGF21 - Arintaya Phrommintikul (2018)
© 2018 The Author(s). Increased fibroblast growth factor 21 (FGF21) levels have been found in patients with metabolic syndrome (MetS). MetS is also associated with cognitive decline. However, the correlation between FGF21 and cognitive decline in elderly and nonelderly MetS patients has not been investigated. 116 non-elderly patients (age <65 years old) and 96 elderly patients (≥65 years old) with MetS were enrolled. Blood samples for FGF21 were collected from all participants after 12-hour fasting. Cognitive function was assessed using the Montreal cognitive assessment (MoCA) test. The MoCA score was negatively associated with age and was different among different levels of education in these MetS patients. In the non-elderly group, body mass index (BMI) showed positively correlated with MoCA score while, FGF21 level and HbA1C were negatively associated with the MoCA score in non-elderly MetS patients. BMI was the only factor which showed a negative correlation with the MoCA score in elderly MetS patients. This study demonstrated that FGF21 level was independently associated with cognitive impairment in non-elderly patients but not in elderly patients. The possible role of FGF21 level in cognitive impairment in non-elderly should be confirmed in a prospective study.